PENENTUAN CADANGAN PREMI UNTUK ASURANSI PENDIDIKAN - ARIASIH, MADE PUTRI; JAYANEGARA, KETUT; WIDANA, I NYOMAN; N. KENCANA, I PUTU EKA (E-Jurnal Matematika, 2015)
This aims of this research is determine the insurance premium reserve for education with retrospective calculations and determine the premium reserves who acquired during the period of guarantee for insurance education. This research  observes the premium reserve for persons aged 40 years with a coverage period of 17 years. The secondary data used is an education insurance data product  from the insurance company that issued the insurance product. Premium reserve is determined by using the retrospective calculation, the calculation using the annuity value, net single premium value, net annual premiums, the value of net monthly premium, CSO 1980 mortality and fixed interest rate at 9%. Retrospective calculations produce a faster value backup  and sequentially in each year. The results showed that the premium reserve with retrospective calculation should be close up to the cash price owned by insurance company and must be the same at the end of the insurance period is Rp 7.000.000,00.
Keywords: education insurance; the premium reserve; a retrospective